After 50 Years: Divine Revelation; Sacred Liturgy - Shaji George Kochuthara, CMI (Asian Horizons, 2013)
On the occasion of the jubilee of the great event of the Second Vatican Council, Asian Horizons has dedicated a few issues to reflection on the Council, its contributions and continuing relevance. March 2013 issue reflects on two of the constitutions of the Second Vatican Council, namely, Dei Verbum and Sacrosanctum Concilium. Both these documents have their own uniqueness. Sacrosanctum Concilium was the first constitution to be promulgated. Dei Verbum on the other hand, has an interesting history, as the original schema was rejected and rewritten, and the text was thoroughly reworked. Both these documents have been exerting great influence in the renewal of the Church. Besides reflecting on the historical background and formation of these documents, theologians critically reflect on the teaching given in these documents and their continuing relevance. Post-conciliar developments in biblical interpretation and liturgical theology and the present day challenges also are addressed.